2023
DOI: 10.1039/d3sm00628j
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic temperature-dependent structural dynamics in polymer nanocomposites: role of the graft–matrix chain interfacial entropic effect

Abstract: We present a systematic study of the structural dynamics in bulk polymer entropic nanocomposites (PNCs) with polymer grafted nanoparticles (PGNPs) using quasi-elastic neutron scattering (QENS). We observe that the wave...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(135 reference statements)
0
1
0
Order By: Relevance
“…[19][20][21][22][23] The reinforcing effect of CB on the polymer matrix has been extensively studied; see, for example, [24][25][26] controlling the interphase between the filler particles and polymer chains, for example, bound rubber in CB or carbon nanotube (CNT) filled rubber, has been a recurrent theme in the study of PNC because many observations have shown that it can significantly impact the effective mechanical properties of the samples. [27][28][29][30][31][32][33] As was recalled above, we can go beyond the mechanical characterization because the interfacial properties of PNC can be probed by a large variety of scattering and microscopy techniques with the aim of identifying their characteristic length and time scales, for example, NMR, [3,10,11,34,35] differential scanning calorimetry (DSC), [36] dynamic mechanical thermal analysis (DMTA), [28,[37][38][39] rheology, [40,41] neutron and positron annihilation spectroscopies, [42,43] atomic force microscopy (AFM), [26,40] small-angle neutron (SANS), [42,43] and small-angle X-ray scattering (SAXS). [44][45][46] One important question in this field concerns the observed similarities amongst PNC.…”
Section: Characterization Of the Interface Between Phases In Dense Po...mentioning
confidence: 99%
“…[19][20][21][22][23] The reinforcing effect of CB on the polymer matrix has been extensively studied; see, for example, [24][25][26] controlling the interphase between the filler particles and polymer chains, for example, bound rubber in CB or carbon nanotube (CNT) filled rubber, has been a recurrent theme in the study of PNC because many observations have shown that it can significantly impact the effective mechanical properties of the samples. [27][28][29][30][31][32][33] As was recalled above, we can go beyond the mechanical characterization because the interfacial properties of PNC can be probed by a large variety of scattering and microscopy techniques with the aim of identifying their characteristic length and time scales, for example, NMR, [3,10,11,34,35] differential scanning calorimetry (DSC), [36] dynamic mechanical thermal analysis (DMTA), [28,[37][38][39] rheology, [40,41] neutron and positron annihilation spectroscopies, [42,43] atomic force microscopy (AFM), [26,40] small-angle neutron (SANS), [42,43] and small-angle X-ray scattering (SAXS). [44][45][46] One important question in this field concerns the observed similarities amongst PNC.…”
Section: Characterization Of the Interface Between Phases In Dense Po...mentioning
confidence: 99%